2021
DOI: 10.3389/feart.2020.542391
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Biomass and Production of the Macrophytobenthos in two Lagoons in the Southern Baltic Sea

Abstract: Baltic coastal lagoons are severely threatened by eutrophication. To evaluate the impact of eutrophication on macrophytobenthos, we compared the seasonal development in macrophytobenthic composition, biomass and production, water column parameters (light, nutrients), phytoplankton biomass and production in one mesotrophic and one eutrophic German coastal lagoon. We hypothesized that light availability is the main driver for primary production, and that net primary production is lower at a higher eutrophication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 76 publications
1
14
0
Order By: Relevance
“…Secondly, the share of waterborne POC compared to macrophyte POC ranged from 22-67% at the end of the experiment (S2 Fig) . These results indicated that phytoplankton production can be as high as macrophyte production in shallow areas. Similar results were described in a recent field study where seasonal net carbon production rates of phytoplankton in the eutrophic DZLS were comparable to macrophyte production in a mesotrophic lagoon in close proximity [63]. This mechanism can be missed, due to dilution, grazing on phytoplankton and macrophytes, or burial of biomass in the actual ecosystem.…”
Section: Effects Of Temperature Nutrients and Light On Primary Productionsupporting
confidence: 89%
“…Secondly, the share of waterborne POC compared to macrophyte POC ranged from 22-67% at the end of the experiment (S2 Fig) . These results indicated that phytoplankton production can be as high as macrophyte production in shallow areas. Similar results were described in a recent field study where seasonal net carbon production rates of phytoplankton in the eutrophic DZLS were comparable to macrophyte production in a mesotrophic lagoon in close proximity [63]. This mechanism can be missed, due to dilution, grazing on phytoplankton and macrophytes, or burial of biomass in the actual ecosystem.…”
Section: Effects Of Temperature Nutrients and Light On Primary Productionsupporting
confidence: 89%
“…Periphyton (Sañudo‐Wilhelmy et al, 2004) and possibly charophytes (Kufel & Kufel, 2002) can take up large amounts of dissolved nutrient that occur frequently through diffuse runoff (Berthold, Karstens, et al, 2018). Tracheophytes in the DZLS and adjacent lagoons can show high colonization rates by epiphytes (Paar et al, 2021), offering an additional plant food source to gammarids. Nonetheless, charophytes in the DZLS showed higher C:N and N:P ratios than tracheophytes, making them more likely to gammarid grazing as high‐value food (Appendix S1: Figure S7).…”
Section: Discussionmentioning
confidence: 99%
“…These broader temperature acclimation abilities may help to permanently introduce G. tigrinus within the Baltic Sea, as sea surface temperature is already higher there than in other ocean parts (Reusch et al, 2018). Furthermore, the endurance of hypoxic conditions is an advantage in eutrophic coastal waters of the Baltic, as redox conditions within the reed belt and adjacent macrophyte stands can change fast (Berthold & Paar, 2021; Karstens et al, 2015), and an increase in nutrients is challenging for submerged macrophytes in the coastal water bodies of the southern Baltic Sea (Paar et al, 2021), stressing habitats of native gammarids. On the contrary, an in silico study assumed that G. tigrinus has actually a narrower niche than native gammarids in the northern Baltic Sea (Herkül et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…in the coastal waters of the southern Baltic Sea (Paar et al 2022). This epiphytic grazing is important especially in turbid coastal waters, where macrophytes are already under light limitation, and epiphytic biomass can increase rapidly during summer months (Paar et al, 2021), possibly causing additional stress on macrophytes (Lin et al, 1996; Özkan et al, 2010). The no-fish mesocosm seemed to have less capacities to buffer external nutrient inflows by bulk deposition (Supplement Table 1), because pelagic nutrient stocks increased for both N and P (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Mesograzer like snails can liberate macroalgae from epiphytic growth and recycle necessary nutrients (Bracken et al 2014). This epiphytic grazing is important especially in turbid coastal waters, where macrophytes are already under light limitation, and epiphytic biomass can increase rapidly during summer months (Paar et al, 2021), possibly causing additional stress on macrophytes (Lin et al, 1996;Özkan et al, 2010).…”
Section: Food Web Impact Of Biomanipulationmentioning
confidence: 99%